Science and technology for development : report on the United Nations Conference on the Application of Science and Technology for the Benefit of the Less Developed Areas - United Nations (New York : United Nations, 1963)
This is a report on the United Nations Conference on the Application of Science and Technology for the Benefit of the Less Developed Areas.
"United Nations publication. Sales no. : 63.I.21-[63.I.28]"
lje 16/10/16
Loans
Keywords: Economic development; Science; Technology